Forecasting the level of growth and development of root rots on Hordeum vulgare L. plants - D. Gentosh; L. Havryliuk; O. Bashta; D. Olifer; I. Artemchuk (Карантин і захист рослин)
Goal. To develop short-term forecasting methods for the seasonal development of root rots of spring barley.